Edukasi Pemasaran Digital bagi Pelaku Usaha “Rumah Mandiri” di Desa Sidoharjo, Kulon Progo - Agustina, Tri Siwi; Herachwati, Nuri; Ekowati, Dian; Kusumasondjaja, Sony; Sulistyawati, Chorry; Gunawan, Sri; Khaira, Nurul (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2024)
Sidoharjo Village, Kulon Progo Regency, Yogyakarta Special Region has extraordinary natural resources. In addition, the village has 2 (two) superior products, namely Coffee known as Menoreh Coffee with its rich flavor and Cassava Chips with various flavors. Unfortunately, the marketing is still not optimal. The results of the initial survey were the lack of knowledge and skills about Whatsapp and Instagram for marketing media. The Community Service Team of S1 Management FEB Universitas Airlangga has developed a training and mentoring program for Rumah Mandiri MSMEs to be able to transform into digital marketing. Training and mentoring was carried out from October to December 2024. The results obtained by participants began to show changes in the preparation of posts, image quality, making captions on their social media accounts. It is hoped that after this community service program, MSMEs can be more independent and routine in utilizing their social media to achieve a wider marketing target.